Direct isotopic evidence for subsistence variability in Middle Pleistocene Neanderthals (Payre, southeastern France). (15th December 2016) - Bocherens, Hervé; Díaz-Zorita Bonilla, Marta; Daujeard, Camille; Fernandes, Paul; Raynal, Jean-Paul; Moncel, Marie-Hélène
Abstract: The site of Payre (SE France) is presented as a case study to decipher possible changes in subsistence and land-use strategies during the middle Pleistocene in Europe. This study applies carbon and oxygen isotopic data (δ 13 C and δ 18 O) in dental tooth enamel from four distinct Middle Pleistocene Neanderthals coming from two phases of occupation. This allows us to test if these different Neanderthals were similar in their subsistence strategies and mobility during their childhood, and to compare them with terrestrial predators and to herbivores dwelling in different areas around the cave. The results show that Neanderthals were exploiting the environment differently over time in the absence of a significant environmental change. This change of environment exploitation coincides with different durations of occupation. The age of the individuals allows us to discuss the mobility of young Neanderthals and the topographies they lived on before arriving in the cave. The combination of results obtained from various approaches throws a new light on the investigation of Neanderthal ecosystem and land-use patterns during the Early Middle Palaeolithic in Southeastern France. Highlights: 4 Neandertals from 2 layers in Payre analyzed for C and O isotopes in tooth enamel. Different prey exploitation (valley-plateau) without significant climate change. Coincides with occupation length. New light on ecosystem and land-use pattern by Neandertals.